Effect Of Surface Treatment On The Performance Of Polyester Composite Filled With Waste Glove Rubber Crumbs - Salit, Mohd Sapuan; Mustafa, Nuzaimah; Razali, Nadlene; Mohammad Jawaid (Springer Science and Business Media B.V., 2020)
Abstract: This work evaluates applicable rubber crumbs surface treatments to improve the rubber-polyester composite tensile strength. Generally, the addition of untreated rubber crumbs to composites resulted in strength loss because of weak adhesion between rubber and polyester. Rubber crumbs were prepared by grinding the waste gloves under cryogenic conditions. The crumbs were subjected to NaOH, H2SO4 and KMnO4 surface treatment and the composites were fabricated by adding the treated rubber to the unsaturated polyester. FTIR, SEM analysis and contact angle measurement were performed on the treated rubber crumbs. The composites were subjected to tensile test and the fracture surface were analyse using SEM. NaOH treatment improved hydrophilic properties of rubber crumbs and enhanced rubber-polyester interfacial adhesion, hence increasing the composite tensile strength by 2% from the untreated rubber. However, for H2SO4 and KMnO4 treatments the tensile strength decreased by 2% and 11% respectively. As hydrophilicity increased, the contact angle of the NaOH treated rubber surface decreased significantly by 30% compared to the untreated rubber surface. Rubber surface with better hydrophilic properties promotes better polyester wetting on the rubber thus enhancing the adhesion between rubber and polyester. The SEM analysis on the NaOH treated rubber reveals a rougher surface with numerous micropores and microcracks that allow the polyester to penetrate into the irregularities of the rubber surface thus induces better adhesion between the two. The FTIR analysis indicates more polar functional groups and soluble elements on the treated rubber surface. These groups initiate more linkages with polyester polar groups, enhancing interfacial adhesion. NaOH also removed the additives passive layer on the rubber surface, hence allowing better polyester coverage. Therefore, the NaOH treatment of waste rubber crumbs improves adhesion between rubber and polyester, which increases the tensile strength of the composite. Graphic Abstract: [Figure not available: see fulltext.